BRAIN BIOPHYSICS: MECHANISMS OF SIGNAL TRANSMISSION BETWEEN NEURONS (Modern American Journal of Medical and Health Sciences, 2025)
This article explores the biophysical foundations of brain activity. It focuses on interneuronal signal transmission and explains mechanisms such as action potentials, ion channels, and information transfer via neurotransmitters at synapses. In addition, it examines the relationship between electrical and chemical processes, biophysical research methods, and their applications in understanding brain signal transmission in health and disease. The article provides students with a scientific basis for understanding neuronal activity and highlights opportunities for applying biophysics in practice.